On the low-cycle fatigue behavior of thermo-mechanically processed high-strength aluminum alloys. (March 2022) - Sajadifar, S.V.; Scharifi, E.; Wegener, T.; Krochmal, M.; Lotz, S.; Steinhoff, K.; Niendorf, T.
Abstract: In the present work low-cycle fatigue experiments were carried out on thermo-mechanically processed AA6082 and AA7075 sheets to evaluate mechanical properties under cyclic loading. Different cooling rates imposed by use of tempered forming tools after solutionizing and subsequent aging treatment led to the formation of precipitates with differing sizes and morphologies. Specimens thermo-mechanically processed in tools with temperatures of 24 °C and 200 °C showed superior mechanical properties under both monotonic and cyclic loading. Different behavior was observed for the specimens formed in the tool with a temperature of 350 °C. Based on thorough analysis of prevalent microstructural features, processing-property-damage relationships are established pointing at the major impact of the thermal history on the final performance of the high-strength aluminum alloys in focus.